Embedded systems design with platform FPGAs principles and practices - Sass, Ronald (Morgan Kaufmann, 2010)
This book will introduce professional engineers and students alike to system development using Platform FPGAs. The focus is on embedded systems but it also serves as a general guide to building custom computing systems. The text describes the fundamental technology in terms of hardware, software, and a set of principles to guide the development of Platform FPGA systems. The goal is to show how to systematically and creatively apply these principles to construction of application-specific embedded system architectures. There is a strong focus on using free and open Source software to increase p.